A study of ethics and information technology usage among UUM international students / Abdul Manaf Bohari and Nurul Hafizan Mazani - Bohari, Abdul Manaf; Mazani, Nurul Hafizan (Universiti Teknologi MARA, Kedah, 2011)
Basically, ethics is a universal entity on guiding beliefs, standards, or ideas that pervades an individual, a group or community of people who are accountable for their actions and behaviors. In the emerging of world of ICT, one is required to behave ethically rights. Ethics of IT users varies according to religions, cultures, and societies; and based on literature review, it depends on beliefs and perceptions. Currently, IT drastically changes the way how ethics is conducted and practised within organizations. Therefore, the main objective of this research is to identify what is perceived as ethical behavior in IT usage. Secondly, this research is to observe the ethics among international students in relation to IT. In order to conduct this research, questionnaire will be used to collect the primary data from respondents, as well as international students of Universiti Utara Malaysia. The data collected will then be analyzed using Statistical Package for Social Science (SPSS) software. This research reveals that, ethics in IT users of different countries such as Indonesia, Thailand, China, Iraq, and Pakistan vary. Mostly, the ethics is based on attitudes and perceptions and to what extent it is said to be ethical in dealing with IT.